(untitled) (Palíndromo, 2024)
This text is part of reflections carried out in years of research on reading audiovisual productions in which we sought to develop a proposal for audiovisual reading for education based on studies on reading images by Ana Mae Barbosa, María Acaso, Arthur Efland, Kerry Freedman, Patricia Stuhr, Fernando Hernández and with the contributions of discursive semiotics, especially the studies of Eric Landowski, Ana Silvia Médola, Yvana Fechine, Nilton Hernandes, Lucia Teixeira, Ramalho e Oliveira on the apprehension of meaning effects in visual and syncretic creations. Such studies provided theoretical and methodological support to understand the meanings that the procedures that articulate the different languages in these productions make possible. In our research we seek to build an audiovisual reading proposal for education and carry it out in different contexts and levels of education, whether in early childhood education, primary education, higher education, in order to improve it. We will present, below, some principles of the reading proposal through the analysis of the advertising film Coleção Era uma vez...Autumn/Winter 2014 Gabriela Aquarela, focusing on the effects of meaning that the editing procedures create and the meanings that a group of university students from a teacher training course made of this creation. The results point to some routes for analyzing audiovisual productions in education.